Classification of Symbol in the Poetics of Modern Uzbek Stories (Eurasian Scientific Herald, 2022)
The article talks about the place of symbol and symbolism in the poetics of the work, which is a type of speech movement in the genre of the current short story. Also, the principles of classification of existing symbols in the stories analyzed as an object were researched. This classification was made mainly according to the composition of the work.